Consumer Preferences and Attitudes in Purchasing Cavendish Bananas of the “Sunpride” Brand at Lotte Mart Pakuwon Mall Surabaya (Fishbein Multiattribute Model Approach) - Ratnakanyaka, Meimy; Hendrarini, Hamidah; Tondang, Ika Sari (Tarjih : Agribusiness Development Journal, 2025)
The growth of fresh fruit consumption in Indonesia, especially bananas, is influenced by public awareness of health and product quality. However, there is a problem in the form of a decline in banana consumption in the city of Surabaya during the period 2021–2024. This study aims to identify consumer characteristics and preferences for purchasing "Sunpride" Cavendish bananas at Lotte Mart Pakuwon Mall Surabaya. The research method used is quantitative with primary data collection through questionnaires and interviews with 100 respondents, then analyzed using descriptive analysis and the Fishbein multi-attribute technique covering seven attributes (color, taste, price, size, freshness, number of bananas per bunch and type of banana). The results show that the majority of consumers are women, productive age 20-43 years, have a bachelor's degree, are self-employed, and have a high income. The most considered banana attribute is freshness (Ao= 3.42), followed by sweetness (Ao= 2.80) and yellowish-green color (Ao= 2.70), while price, type, and size are secondary considerations. This indicates that consumers prioritize fruit quality over attributes such as price. This research provides input for the company and Lotte Mart to maintain product quality, especially freshness, taste, and color, and adjust offerings according to consumer needs to maintain loyalty.